Computational investigation of various wedges electromagnetic wave absorbers on anechoic chambers - Naufal Baihaqi Al Afkar (Universitas Mercu Buana, 2022)
The anechoic chamber is closely related as a device for precisely measuring various acoustic characteristics. Anechoic chambers room conditions controlled to produce a sound field-free space. This study focused on testing various commercial wedges such as Eckel, diamond, pyramidal, and oblique pyramidal. The test was done by varying the elevation of an incident angle at 0°-85° with a stepping distance is 5°. This study is analyzed at 1-3 GHz frequency. This research was conducted based on a computational analysis using the finite element method on electromagnetic wave physics interfaces using COMSOL Multiphysics. The results show that, in general, pyramidal has the best performance. These results are assessed from the stability of absorption performance, the Eckel model obtains -66.6 dB at 1 GHz frequency but on another frequency tests with drastic performance fluctuations. In general, a pyramidal model can be an ideal absorber for anechoic applications because it provides good absorption performance for near normal and normal incidence angles. The results of the design and testing of the wedges model for anechoic are expected to be references in designing the optimal anechoic chamber room. Furthermore, it can contribute positively to tuning acoustic instruments such as microphones or reducing the antenna measurement error.